Implementation of Principal's Democratic Leadership Style to Improve Teacher Participation in Decision Making at State Elementary School 012 Naumbai - Romenza, Lufia; Azhar, Azhar; Erni, Erni (CV. Tripe Konsultan, 2024)
This study aims to analyze the implementation of the democratic leadership style of the principal at SD Negeri 012 Naumbai, identify the causes of the lack of teacher participation in decision-making, and analyze the implications of the implementation of this leadership style on the level of teacher participation. In this study, the approach used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The data obtained were then analyzed through three stages: data collection, data presentation, and drawing conclusions. The results of the study indicate that the principal at SD Negeri 012 Naumbai has implemented a democratic leadership style well and consistently. The principal actively involves teachers and education personnel in the decision-making process through deliberation and open discussion, providing space for teachers to express their opinions and ideas. Thus, the principal positions teachers as working partners who have an important role in the progress of the school, which creates a more open, participatory, and harmonious working atmosphere. This is more due to internal factors such as previous work habits that tend to be more hierarchical, limited experience in decision-making, and lack of initiative from the teachers themselves, not because of the lack of support or opportunity from the principal. The implications of the implementation of democratic leadership, although not yet fully optimal, show a positive impact on the work climate in schools. Gradually, teacher participation in decision-making increases, which leads to an increased sense of shared responsibility, team cohesion, and more effective implementation of school programs. The school environment also becomes more open and collaborative, supporting the creation of healthy school management that is oriented towards mutual progress.